PERAN GURU DALAM MENGINTERNALISASIKAN NILAI- NILAI MORAL SOSIAL PEMBELAJARAN IPS SMPN 22 PONTIANAK - Norsita Norsita; Sulistyarini Sulistyarini; Izhar Salim (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2021)
AbstractThis study aims to explain the teacher's role in internalizing social moral values insocial studies learning in class VII A SMPN 22 Pontianak". The research methodused is descriptive method in the form of qualitative research. The data collectiontechniques used were observation, interviews and documentation studies, while thedata collection tools were observation guides, interview guides, documents andcameras. Informants in this study were social studies teachers and students of classVII A SMPN 22 Pontianak. The results of the study show that 1. The teacher's roleas educator in internalizing social moral values has been carried out by theteacher in the classroom well, this is evidenced by preparing learning designs withvaried learning methods. 2. The role of the teacher as a guide in internalizingsocial moral values has been realized such as guiding students to obey the rules atschool, advising students if they commit violations and providing encouragement toraise students' enthusiasm for learning. 3. The role of the teacher as an example ininternalizing social moral values by setting an example for students by behavingwell, and using polite and courteous language.Keywords: Teacher's Role, Internalization, Social Moral Values.